CUSTOMER WILLINGNESS TO PAY APLIKASI MUSIK JOOX REGULER DI INDONESIA - Marvin Lee; Dhyah Harjanti (Institute of Research and Community Outreach - Petra Christian University, 2022)
This study examined the role of attitude toward paying, along with subjective norms and perceived behavioral control, to form the willingness of Indonesian consumers to pay Joox music application. Data were gathered by disseminating questionnaires to 394 respondents, then were analysed using Partial Least Square (PLS). The findings confirmed that perceived benefit, perceived sacrifice, and free mentality had a significant influence on attitude toward paying. The results also showed that attitude toward paying, subjective norm, and perceived behavioral control on customer willingness to pay. Abstrak: Penelitian ini menguji peran attitude toward paying bersama-sama dengan subjective norm dan perceived behavioral control terhadap customer willingness to pay pengguna aplikasi musik Joox di Indonesia. Data penelitian ini diperoleh dengan mendistribusikan kuesioner pada 394 responden, lalu diolah menggunakan Partial Least Square (PLS). Dari penelitian ini dapat disimpulkan bahwa perceived benefit, perceived sacrifice, dan free mentality berpengaruh terhadap attitude toward paying. Hasil penelitian juga menunjukkan bahwa attitude toward paying, subjective norm, dan perceived behavioral control membentuk kesedian konsumen untuk membayar aplikasi music Joox.